Laparoscopic cholecystectomy under spinal anesthesia in high risk patients: A single center experience (Annals of Medical Research, 2021)
None
Keywords: Laparoscopy; Cholecystectomy; Spinal Anesthesia; Gallstone Disease; Regional Anesthesia.